Divergent NEE balances from manual‐chamber CO2 fluxes linked to different measurement and gap‐filling strategies: A source for uncertainty of estimated terrestrial C sources and sinks?1. Issue 3 (28th March 2017) - Huth, Vytas; Vaidya, Shrijana; Hoffmann, Mathias; Jurisch, Nicole; Günther, Anke; Gundlach, Laura; Hagemann, Ulrike; Elsgaard, Lars; Augustin, Jürgen
Abstract: Manual closed‐chamber measurements are commonly used to quantify annual net CO2 ecosystem exchange (NEE) in a wide range of terrestrial ecosystems. However, differences in both the acquisition and gap filling of manual closed‐chamber data are large in the existing literature, complicating inter‐study comparisons and meta analyses. The aim of this study was to compare common approaches for quantifying CO2 exchange at three methodological levels. (1) The first level included two different CO2 flux measurement methods: one via measurements during mid‐day applying net coverages (mid‐day approach) and one via measurements from sunrise to noon (sunrise approach) to capture a span of light conditions for measurements of NEE with transparent chambers. (2) The second level included three different methods of pooling measured ecosystem respiration (RECO ) fluxes for empirical modeling of RECO : campaign‐wise (19 single‐measurement‐day RECO models), season‐wise (one RECO model for the entire study period), and cluster‐wise (two RECO models representing a low and a high vegetation status). (3) The third level included two different methods of deriving fluxes of gross primary production (GPP): by subtracting either proximately measured RECO fluxes (direct GPP modeling) or empirically modeled RECO fluxes from measured NEE fluxes (indirect GPP modeling). Measurements were made during 2013–2014 in a lucerne‐clover‐grass field in NE Germany. Across the different combinations of measurement and gap‐filling options, the NEE balances of the agricultural field diverged strongly (–200 to 425 g CO2 ‐C m −2 ). NEE balances were most similar to previous studies when derived from sunrise measurements and indirect GPP modeling. Overall, the large variation in NEE balances resulting from different data‐acquisition or gap‐filling strategies indicates that these methodological decisions should be made very carefully and that they likely add to the overall uncertainty of greenhouse gas emission factors. Preferably, a standard approach should be developed to reduce the uncertainty of upscaled estimates.